Utility of PCR in the Diagnosis of Tubercular Lymphadenitis on Fine Needle Aspirates - Fernandes, Hilda; Shetty, Anup Kumar; ., Archana (Annals of Pathology and Laboratory Medicine, 2022)
Background Extra-pulmonary tuberculosis is a diagnostic and therapeutic challenge. Diagnosing tubercular lymphadenitis includes identification of epithelioid granulomas, positive Acid Fast Bacilli detected with Ziehl Neelsen’s stain. The disadvantage is the time taken for formation of granulomas. With the advent of RT-PCR, the diagnosis of tubercular lymphadenitis can be made with ease [1]. Aims and objectives: To utilize PCR and mycobacterial culture on samples obtained from Fine needle aspiration of lymph nodes in order to aid in early diagnosis of extra-pulmonary tuberculosis. Materials and methods: Observational descriptive prospective study; Patients with lymphadenopathy >1 cm, above the age of 2 years were included ; FNA was performed, material was used for routine cytological studies (PAP, MGG and Ziehl Neelsen-stained slides), PCR and culture (wherever possible); Comparative values of PCR and culture were utilized for statistical analysis Results: Out of 80 cases studied, M. Tuberculosis by PCR was detected on 36 cases (45%); PCR and culture demonstrated MTB in 42.55% of the cases. 9 cases (11.25%) of reactive lymphadenitis were found to be of tubercular etiology on PCR analysis. The Chi-squared test was highly significant. PCR has been found to have a sensitivity, specificity, PPV and NPV of 100%, 92.59%, 90.91% and 100%, respectively. Positive RT-PCR was more common in cases with chronic granulomatous inflammation when compared against reactive lymphoid hyperplasia with a chronic inflammatory infiltrate. Conclusion: From this study, we conclude that RT-PCR is a useful ancillary technique to conclusively identify Mycobacterium tuberculosis in samples obtained from fine needle aspiration of lymph nodes.